The Social Generalist's Dilemma - Melvyn L. Fein (Journal of Public and Professional Sociology)
We humans are social generalists. Our behavior is open to modification, but potential changes are constrained by the requirements of social cohesion. This exposes us to a dilemma. A concurrent need to be both flexible and stable introduces inescapable conflicts. Moreover, the biological mechanisms that evolved to meet this challenge produce their own contradictions. Thus, while social hierarchies can be functional, they can also be divisive. Whereas they allow us to collaborate on complex projects, they may produce both arrogance and follies that interfere with flexibly resolving disputes. Morality too, although it is designed to control interpersonal conflicts, can exacerbate them. The orthodoxies and idealism that result from our efforts to make necessary adjustments often have the opposite effect. As a consequence, the social generalist’s dilemma is never fully eliminated. It remains as a limitation on how effective social reforms can be.